2013
DOI: 10.1007/s00146-013-0472-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards empathy: a human-centred analysis of rationality, ethics and praxis in systems development

Abstract: Functionalism has long been the dominant paradigm in systems development practice. However, functionalism promotes an innate and immutable instrumental rationality that is indifferent to human values, rights, society, culture and international stability. It, in essence, lacks empathy. Although alternative paradigms have been promoted for decades in the systems development literature to help address this deficit, functionalism remains dominant. This paper reiterates the call for a fundamental paradigm shift awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…IS research has been dominated by the rational-cognitive approach [2] or instrumental rationality [4].…”
Section: Moodmentioning
confidence: 99%
“…IS research has been dominated by the rational-cognitive approach [2] or instrumental rationality [4].…”
Section: Moodmentioning
confidence: 99%
“…Research has shown that engineers' pessimist beliefs about the feasibility of information privacy come with a decreased motivation to implement privacy mechanisms [28,29]. Carew and colleagues express even wider concerns by showing that in system development, interests in human, social, and moral issues are diametral to interests in technical issues and functionality [30]. Thus, a sustainable model of technology production, use, and interaction needs to conciliate technical values with individual, social, and environmental values.…”
Section: Discovering Human Values In Technologymentioning
confidence: 99%
“…Schwartz's Universal Values Model utilises a form of principle components analysis to configure value patterns within complex organisational and social settings. Whilst this work remains in its infancy, Carew & Stapleton (2014) and Martin (2012) show how such an approach can provide extremely powerful lenses by which to access deep value patterns.…”
Section: Control Engineering and Institutional Dysfunctionmentioning
confidence: 99%
“…They too come laden with assumptions and limitations and good science will need to explicate these. Notwithstanding this, Carew & Stapleton (2014) and Schwartz (1992) have demonstrated the efficacy of these techniques in their models of human cultural value systems.…”
Section: Synthesismentioning
confidence: 99%